Victim in Criminal Procedure: from Victim to Active Subject of Prosecution (Legislation Changes Dynamics Study) - O. A. Voltornist (Сибирское юридическое обозрение, 2014)
The article deals with the stages of the Russian legislation development in respect to procedural status of victim. The research carried out covers the period from 1864 to 1960 and includes the analysis of the main normative and legal acts through the prism of modern legislation concerning a victim.